Contact Angle Based Dielectric Strength Enhancement of Contaminated Ceramic Insulators Using Epoxy-SiO2 Coating - Martini Martini; Yusreni Warmi; Sitti Amalia (Universitas Pendidikan Nasional, 2026)
This study evaluates the effectiveness of epoxy-SiO2 coatings in enhancing the dielectric strength of contaminated ceramic insulators through contact angle analysis. Insulators in tropical regions, such as the 150 kV Koto Panjang-Payakumbuh line, often suffer from performance degradation due to moss contamination and high humidity, leading to reduced hydrophobicity and an increased risk of flashover. Contact angles were measured using the sessile drop method before and after coating. Uncoated insulators exhibited hydrophilic behavior with contact angles below 90° (53.81°, 72.70°, and 60.14°). Pure epoxy improved the values to 87.52°, 91.62°, and 85.94°, indicating partial hydrophobicity. The addition of SiO2 nanoparticles further increased the values above 100° (100.26°, 99.33°, and 101.33°). Based on the empirical correlation between contact angle and dielectric strength, dielectric performance improved from 124.4 kV/cm (uncoated) to 176.7 kV/cm (epoxy) and 200.4 kV/cm (epoxy-SiO2). The novelty of this work lies in demonstrating, for the first time, the comparative effectiveness of epoxy and epoxy-SiO2 coatings under real tropical contamination conditions. These findings confirm that epoxy-SiO2 coatings not only improve hydrophobicity but also provide a homogeneous protective layer, thereby reducing leakage current and strengthening dielectric endurance. The results highlight a cost-effective preventive maintenance strategy with both scientific and practical contributions for high-voltage transmission systems in tropical environments.